(untitled) (Bangladesh Journal of Microbiology, 2019)
Microbial fuel cell (MFC), recently, is considered as a promising alternative to traditional power sources as it can use microorganisms to transform chemical energy of organic compounds into electricity. In future, microbial production of electricity may become an important form of bioenergy because electricity extraction is possible through MFC using wide range soluble or nonsoluble complex organic wastes as a renewable biomass. In this study, single chamber MFC and double chambers MFCs were used to production and enrichment a microbial consortium for electricity generation from organic waste samples. Potential electrogenic bacteria were also isolated from anode, analyzed and evaluated. Most of them were Gram negative and fermentative organisms. Their electrogenic role was promising generating upto 5.05 volts and 4.72 mA when combined five) double chambers in series connection. Isolation of these bacteria and employing these for generation of electricity may bring potential power sector endeavor in future. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 23-26